Secrets for a Successful Dissertation. - Fitzpatrick, Dr. Jacqueline (SAGE Publications, 1998)
This book, designed to help doctoral students carry out and complete a successful dissertation, offers a motivational guide to assist in every step of the process. The authors offer a view of the dissertation process which takes students through the doctoral proposal to the formal defense of the dissertation, and which goes beyond the academic by addressing the emotional and mental stress engendered by the process itself.